Kejahatan Pornografi Upaya Pencegahan dan Penanggulangannya di Kabupaten Ponorogo - Irma Rumtianing Uswatul Hanifah (Justicia Islamica, 2013)
The government has issued Law No. 44/2008 on pornography. One of the objectives of the law is to realize and maintain an ethical society, to have a noble personality, to uphold the values of God Almighty, and to respect the dignity of humanity. In its development, pornographic material has experienced rapid growth andand spread rapidly along with the development and advancement of information and communication technology. The circulation and dissemination of pornographic films is now increasingly rapid because it is supported by the sophistication of information and communication facilities, one of which is the internet media that can be accessed by the public at any time. The following paper will examine how the efforts and strategies carried out by the Ponorogo District Government in preventing and overcoming pornographic crimes in Ponorogo District, what are the obstacles and solutions in preventing and overcoming pornographic crimes in Ponorogo District and how policy formulation for the prevention and overcoming of pornographic crimes in Ponorogo District.